If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(x + 6) = 9 + -12x Reorder the terms: 0.5(6 + x) = 9 + -12x (6 * 0.5 + x * 0.5) = 9 + -12x (3 + 0.5x) = 9 + -12x Solving 3 + 0.5x = 9 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 3 + 0.5x + 12x = 9 + -12x + 12x Combine like terms: 0.5x + 12x = 12.5x 3 + 12.5x = 9 + -12x + 12x Combine like terms: -12x + 12x = 0 3 + 12.5x = 9 + 0 3 + 12.5x = 9 Add '-3' to each side of the equation. 3 + -3 + 12.5x = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 12.5x = 9 + -3 12.5x = 9 + -3 Combine like terms: 9 + -3 = 6 12.5x = 6 Divide each side by '12.5'. x = 0.48 Simplifying x = 0.48
| 4.7x-10.36=7.5 | | 180/3750= | | -6x+3+2x=11 | | y=1/4-11/4 | | 8j/7-4j | | 40=(2-3x)x | | .9*35= | | 6(d-9)=3(14-d) | | (10b-1)-3(3b+1)=-5 | | 6-1=X | | 5k-4+3n=6 | | 4(x+1)+2(3x-7)= | | 1+N-3=-8 | | 300/270= | | -9-X=-15 | | 270/300= | | -3=6b-1-2 | | 6x+6x+4+9=8x+5+3x | | -6(4b+3)+(25b-3)=0 | | 4(x^3)-484x=0 | | 2x-3x=-3 | | bx+b=ba+b | | 0.25(z-4)=z+8-2z | | 2-m-3m=-2 | | 4x+3x=-2x+29 | | 55.85*4= | | 35=5x+4x+7 | | -44x+28y+4=0 | | 2=x-2+3 | | -3=5m-6m | | (-15)(-11)= | | 14m-10=3(4-m) |